2018
DOI: 10.1002/ird.2222
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Farmers in a Research Project. Lessons Learned from Implementing the Community of Practice Concept in Innovation Platforms in Irrigated Schemes in Tunisia, Mozambique and Ethiopia

Abstract: The role of smallholder farmers in multi‐stakeholder innovation platforms and thus in the innovation process that these platforms facilitate is typically limited. The EAU4Food project, aimed at increasing food production in irrigation schemes in Africa through improved farming strategies, used a platform design inspired by the community of practice (CoP) concept, which opened up space for farmers' interactive learning and enabled their active participation in the innovation process. In this article we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The reluctance of farmers to participate regularly in meetings seemed high and the research team was facing difficulties in getting them involved. Working with a random group of individual farmers instead of informal dialogue groups could fail to bring the expected results (Dolinska et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The reluctance of farmers to participate regularly in meetings seemed high and the research team was facing difficulties in getting them involved. Working with a random group of individual farmers instead of informal dialogue groups could fail to bring the expected results (Dolinska et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated by Dolinska et al (, in preparation), the level of participation in the present case study according to the scale of participation adapted after Pretty () can be considered as giving opinion in the diagnosis and definition of the research agenda, interactive participation in identifying the innovation to be tested and planning of the innovation test, and self organization in conducting the innovation test. This means that there was a progressive increase in the level of participation in the innovation process.…”
Section: Discussionmentioning
confidence: 98%
“…A comparative analysis of case studies from Ethiopia, Mozambique and Tunisia revealed that working on the already existing groups and building on prevalent formal dialogue groups is very helpful to create learning communities (Dolinska et al ., ).…”
Section: Engaging With An Extended Non‐scientific Peer Communitymentioning
confidence: 97%
“…Dolinska et al . () highlighted the readiness, in particular of researchers, to participate in the transdisciplinary process. Important learning has taken place for all participating researchers in the EAU4Food project.…”
Section: Engaging With An Extended Non‐scientific Peer Communitymentioning
confidence: 99%
See 1 more Smart Citation